Masonry and residential building in Germany: Status 2019 and forecast for 2021. Issue 2 (12th April 2019) - Rast, Ronald
Abstract: Rund 80 % aller Produkte der Mauersteinindustrie in Deutschland gehen in den Wohnungsneubau. Nimmt man die Produkte für die Sanierung von Wohngebäuden mit dazu, finden über 85 % aller Mauerwerksprodukte ihre Verwendung im Wohnungsbau. Aus Sicht der Wohnungsbautätigkeit ist mit leicht steigender Tendenz innerhalb der letzten sechs Jahre feststellbar, dass rund 73 % aller Wohnungsbauten in Deutschland überwiegend mit Konstruktionen aus Mauerwerk errichtet wurden. Tabelle 1 zeigt die Marktanteilsentwicklung der verschiedensten Bauweisen Stahlbeton‐, Mauerwerks‐ und Holzbau über die Jahre 2012 bis 2017. Abstract: About 80 % of all products of the masonry industry in Germany are used for new residential building. If products for the refurbishment of masonry buildings are added to this, then over 85 % of all masonry products are used in residential building. Regarding residential building activity, it can be stated that about 73 % of all residential buildings in Germany are of predominantly masonry construction, with a slightly increasing tendency. Table 1 shows the development of market shares of the various construction methods reinforced concrete, masonry and timber over the years 2012 to 2017.